Yellow in Black and White: Representasi Identitas Asia oleh Rich Brian dalam Musik Hip-Hop di Amerika Serikat - Nokia Putri Andika Lainsyamputty (Universitas Gadjah Mada, 2021)
The representation of the Asian race in the US music industry is still relatively small. However, Rich Brian, a person of Chinese descent with Indonesian nationality, succeeded in his career by carrying out the hip-hop genre that was firmly rooted in African-American (black) racial groups in the United States, a country which was dominated by Caucasian (white) races. This study aims to uncover how Brian represented his identity in the US hip-hop music scene using Stuart Hall's circuit of culture theory. The object of this research is the lyrics of several songs in Rich Brian's album. Through the analysis process, it was found that Brian did not cover the nationality and race identity he had. He precisely positioned himself on the spectrum of social identity. This then affects the representation of identity that he does in his songs, including revolving around the theme of the meaning of identity and stereotypes of the Asian race, as well as the struggles experienced by Asians who are part of minority groups in the United States.